Efficacy of Goniotomy With Kahook Dual Blade in Patients With Uveitis-associated Ocular Hypertension. Issue 8 (August 2019) - Miller, Victoria J.; Young, Cara E. Capitena; SooHoo, Jeffrey R.; Seibold, Leonard K.; Kahook, Malik Y.; Pecen, Paula E.; Palestine, Alan G.; Pantcheva, Mina B.
Abstract : Precis: In a small case series of patients with uveitis-associated ocular hypertension (OHTN) or glaucoma, goniotomy with Kahook Dual Blade (KDB) was an effective surgical treatment option for lowering intraocular pressure (IOP). Purpose: The purpose of this study is to review the success of goniotomy using the KDB with trabecular meshwork (TM) excision in lowering the IOP of patients with uveitis-associated OHTN or glaucoma. Materials and Methods: A retrospective chart review was completed for all patients with uveitis-associated OHTN or glaucoma who underwent KDB goniotomy with TM excision alone or in combination with phacoemulsification cataract surgery at a single institution. The study included 12 patients (16 eyes). Patients were followed for a minimum of 5 months postoperatively. The main outcome measures of this case series included postoperative IOPs, percent IOP reduction, and reduction of glaucoma medications. Results: The mean maximum IOP of the patients before maximum-tolerated medical therapy or surgery was 35.6±5.8 mm Hg. The mean preoperative IOP at the clinical office visit before surgery of these patients was 28.1±8.5 mm Hg on maximum-tolerated medical therapy. Ten eyes (62.5%) have maintained an IOP at or below their goal through their most recent follow-up visit (mean follow-up time of 9.6±5.6 mo). The mean number of glaucoma medications was significantly reduced from 3.6±0.9 medications to 2.1±1.7 medications, for a mean reduction of 1.5±1.4 medications ( P =0.004). Conclusions: On the basis of this small case series, KDB goniotomy may be a safe, less invasive, and effective first-line surgical alternative for patients with uveitis-associated OHTN or glaucoma refractory to medical therapy. Abstract : Supplemental Digital Content is available in the text.